THE IMPLEMENTATION OF THE HALAQAH METHOD TO ENHANCE STUDENTS’ INTEREST AND COMPREHENSION OF THE BOOK FATHUL QORIB AT AL-HIKMAH ISLAMIC BOARDING SCHOOL, BANDAR LAMPUNG - Muhammad Muhyi; Imam Syafe'i; Eka Prasetiawati (DIDAKTIKA, 2026)
This study is situated within Islamic education, particularly the pedagogy of pesantren in teaching classical Islamic texts (kitab kuning). It aims to analyze the implementation of the halaqah method in enhancing students’ learning interest and understanding of Fathul Qorib at Al-Hikmah Islamic Boarding School, Bandar Lampung. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation involving purposively selected teachers and students. The findings indicate that the halaqah method is implemented through four stages reading, translating, understanding, and arguing forming a hierarchical cognitive process. This method increases students’ learning interest, as shown by active participation and engagement, and improves their understanding, reflected in their ability to explain and relate the material to real-life contexts. However, higher-order thinking skills, particularly argumentation, are not evenly developed among all students. This study contributes by proposing an integrative halaqah-based learning model that combines cognitive, affective, and social dimensions, while emphasizing the importance of students’ foundational linguistic competence. These findings provide a basis for developing more adaptive and contextual models for teaching classical Islamic texts in contemporary Islamic education.